Comparing the taste‐modifying properties of nanocellulose and carboxymethyl cellulose. Issue 5 (4th May 2021) - Manninen, Hanna; Sandell, Mari; Mattila, Saila; Hopia, Anu; Laaksonen, Timo
Abstract : Abstract: The taste‐modifying properties of nanofibrillar cellulose (NFC) and carboxymethyl cellulose (CMC) are compared for the first time. The samples were prepared in the form of gels, with and without added sweet and bitter taste components. As viscosity itself is known to affect taste perception, the viscosities of NFC and CMC samples were set to the same level as shear rates commonly found in the oral cavity. A trained panel of 10 assessors evaluated the bitterness and sweetness of the samples. Further, the assessors were given an opportunity to describe the samples in free words. The taste‐modifying capacities of the thickening agents were at the same level when sweet compounds were added. However, CMC was better able to reduce the bitterness of quinine hydrochloride than NFC, which did not show any bitterness‐reduction ability with the compound. This was unexpected, as our previous studies of NFC showed fairly high binding capacity with quinine. The open‐ended responses revealed that the NFC‐containing samples had an astringent sensation, while certain assessors observed a sensation of saltiness in the CMC samples. This may explain the inability of NFC to mask the bitterness of quinine hydrochloride, as astringency may act as a bitterness enhancer, while saltiness may suppress it. Both thickening agents were perceived as slightly bitter. Our study reveals the need for further assessment of the orosensory properties of NFC, particularly the magnitude and origin of its astringency, before it can be fully utilized in food industry applications.